FIELD ETHNOGRAPHIC MATERIALS ON RITUAL CULTURE OF KUBACHI PEOPLE - Gadzalova, F A (History, Archeology and Ethnography of the Caucasus, 2016)
The article covers different forms of ritual culture of the residents of the village of Kubachi. The author presents calendar customs associated with the beginning of spring and onset of summer, describes one of the brightest characters in the wedding ceremony of the Kubachins – the mummer (“pyaltar”), and analyzes his transformation in the ritual culture of the village: from the participant of the performance of the union of unmarried people to the wedding comic character. The author of the article also describes minor forms of ritual culture associated with magical views of the Kubachins. It is noted that many forms of rites survive to this day in the culture of the residents of thevillage of Kubachi.
Keywords: Dagestan; Kubachi; ceremonial culture; calendar holidays; wedding; mummers; minor forms of ritual ceremonial actions